2019
DOI: 10.1002/jsfa.9853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen‐protected folic acid and rumen‐protected sodium selenite supplementation on lactation performance, nutrient digestion, ruminal fermentation and blood metabolites in dairy cows

Abstract: BACKGROUND Considering the insufficient ruminal synthesis of folic acid (FA), the higher degradability of FA, and the reduction of sodium selenite (SS) by ruminal microbes into non‐absorbable elemental Se, this study evaluated the effects of rumen‐protected FA (RPFA) and rumen‐protected SS (RPSS) on lactation performance, nutrient digestion and blood metabolites in dairy cows. RESULTS Dry matter (DM) intake and milk composition were unaltered, milk and milk fat yields were higher for both supplements, and milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…On the other hand, the molar proportion of butyrate was higher in the rumen of cows, bulls, and rams fed different Se supplements than in the rumen of animals fed basal diet [25,69,79]. In contrast, rumen-protected sodium selenite (4.8 mg/cow/day) or coated sodium selenite (0.1, 0.2, or 0.3 mg/kg DM) supplementation reduced the molar proportion of butyrate in the rumen of dairy cows compared with non-treatment [26,77]. Moreover, the molar proportion of acetate was lower in dairy bulls fed sodium selenite and coated sodium selenite compared with animals receiving the basal diet [79].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, the molar proportion of butyrate was higher in the rumen of cows, bulls, and rams fed different Se supplements than in the rumen of animals fed basal diet [25,69,79]. In contrast, rumen-protected sodium selenite (4.8 mg/cow/day) or coated sodium selenite (0.1, 0.2, or 0.3 mg/kg DM) supplementation reduced the molar proportion of butyrate in the rumen of dairy cows compared with non-treatment [26,77]. Moreover, the molar proportion of acetate was lower in dairy bulls fed sodium selenite and coated sodium selenite compared with animals receiving the basal diet [79].…”
Section: Resultsmentioning
confidence: 88%
“…In one study, Se was supplemented to grass as a fertilizer [25]; in another study, Se was provided to animals orally [76]; and in the rest of the studies, Se was mixed with the diet. As shown in Table 1, different dietary Se species increased total VFA concentrations and molar proportions of propionate in the rumen fluid of dairy cows [24,26,69,77], Holstein bulls [78,79], Holstein dairy calves [80], goats [81,82], sheep [25,73,75,83], and lambs [84,85]. Lambs and sheep fed organic or inorganic Se diet exhibited an increase in the production of ruminal acetate, iso-butyrate, and iso-valerate compared with the control group [83][84][85].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous study, Li and Hou (2007) found that the quantities of fungal zoospores in the culture fluid were significantly higher in sheep than in goats, and that the digestibility of straw dry matter tended to be higher in sheep than in goats. Also, Du et al (2019) observed that larger populations of fungi supported the higher digestibility of neutral detergent fibre and acid detergent fibre in dairy cows, implying that higher populations of fungi in the forestomach could lead to increased lignocellulose digestibility. The higher proportion of fungi in alpacas, as observed in the present study, may be the reason camelids digest poor‐quality roughage more efficiently than sheep (Dulphy & Demarquilly, 1994; Dulphy et al., 1997; San & Bryant, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…glycolysis, GSH metabolism and folate biosynthesis) [105]. In midlactation cows, Du et al [114] observed an increase in milk, FCM and milk protein yields when rumenprotected folate was supplemented for 90 d. They also observed an increase in plasma albumin with FA, suggesting a potential reduction in inflammation. However, no other parameters of inflammation were measured [114].…”
Section: Folic Acidmentioning
confidence: 99%